A Novel Method for Assessing the Impacts of Innovation and Technology Transfer: A Case Study of Brazilian Manufacturers in the Electric Energy Sector - Rodrigo Oliveira Lima; Romulo Gonçalves Lins; Alexandre Acácio de Andrade (BBR: Brazilian Business Review)
This study aims to identify and evaluate the impacts and the results of the innovation and technology transfer process (ITT) in Brazilian manufacturers in the electric energy sector. For this purpose, first, the actions to assess ITT were described, in sequence, the factors involved in it were identified and the critical points were diagnosed. From the previous factors properly determined, then a quantitative research methodology for assessing ITT impacts, which uses data from a questionnaire with specialists of Brazilian industries involved in the projects, was applied. Afterward, a sequence of T-tests is carried out to validate the hypotheses established, by using the survey’s results. The results indicated that the Brazilian industries have not a model to assess the projects and their respective impacts caused by it, and then the proposed methodology can overcome this gap and it can be used effectively in a practical manner.